Tuberculosis and COVID-19: A combined global threat to human civilization - Kanika Patra; Sovona Batabyal; Kashmira Mandal; Dhriti Ghose; Joy Sarkar (Elsevier, 2022)
A new era has begun with the discovery of SARS-CoV-2 in a seafood market in Wuhan, China. The SARS-CoV-2 outbreak has wreaked havoc on health systems and generated worldwide attention. The world's attention was diverted from the treatment of the leading chronic infectious illness, Mycobacterium tuberculosis. The similarities in the performance of the two infectious species had obvious repercussions. Administrative efforts to combat SARS-CoV-2 have weakened the tuberculosis control chain. As a result, progress against tuberculosis has slowed. Thus, the goal of this review is to examine the impact of SARS- CoV-2 on a chronic public health issue: tuberculosis.